Attention to climate change in British newspapers in three attention cycles (1997–2017). Issue 94 (August 2018) - Saunders, Clare; Grasso, Maria T.; Hedges, Craig
Highlights: Political news prompts increase climate coverage more than meteorological ones. Left-wing newspapers are the most sensitive to news prompts. Tabloid newspapers tend to ignore international news prompts. As climate coverage increases so does sensitivity to news prompts. Abstract: Peaks in climate change newspaper coverage have been attributed to key events, such as major international climate change summits, on the basis that these are reported. This approach overlooks the possibility that unreported events have capacity to focus journalists' and editors' attention on climate change. This study considers the extent to which meteorological and political events – derived externally from what is reported in the media itself (some reported, some not) – coincide with attention to climate change in four UK newspapers. We call these events 'news prompts', since they are potential rather than actual news pegs: some are translated into news stories, others are not. The study brings together literatures on agenda-setting, newsroom practices, and the political economy and ideologies of newspapers. We find that the four newspapers we analyse have responded differently to climate-change related events including international policy events and extreme weather. In recent years, The Mail, The Telegraph and The Times have been relatively insensitive to climate change news prompts in comparison to the more left-leaning Guardian . As climate change coverage increases, so does sensitivity to climate news prompts. This suggests that the ideology of newspapers and the political economy of media outlets may drive climate coverage as much as routine newsgathering practices.